Comparative analysis of technical, economic, weight, and size characteristics of horizontal and vertical steam generators for 1000 mw nuclear power plant units - Yefimov, O. V.; Pylypenko, M. M.; Kavertsev, V. L.; Harkusha, T. A.; Sydorkin, Igor Dmytrovych; Chyzhyk, O. V. (Національний технічний університет "Харківський політехнічний інститут", 2024)
A comparative analysis of the technical characteristics and parameters of horizontal and vertical steam generators for reactor installations with water coolant in modern 1000 MW NPP power units has been conducted. It is noted that the peculiarities of the design schemes and constructions of steam generators in NPP power units with water coolants are significantly influenced by the strong dependence between the coolant temperature at the steam generator inlet and the pressure in the reactor circuit. The dependencies of coolant and working substance temperature changes and the amount of heat transferred in steam generator elements have been considered. The t-Q diagram of a steam generator with a water coolant featuring a non-boiling economizer, evaporator, and superheater is presented. The parameters of water coolants and working substances in nuclear power plant steam generators are provided. The t-Q diagram for steam generators without a superheater section is shown, because in modern 1000 MW nuclear power plant units with steam generators which use water as the working substance in the steam-turbine cycle, saturated steam without superheating is used. This is because minor superheating of the steam does not significantly increase the efficiency of the steam-turbine cycle but requires significant complexity in the design of the steam generators. It is noted that the correct choice of their structural schemes is crucial in the creation of steam generators with water coolants. It has been proven that the characteristics determining the structural schemes of steam generators with water coolants are: the scheme of washing the heat exchange surface with the coolant, the form of the heat exchange surface, the layout of steam generator elements, the principle of working substance movement, and others. Виконано порівняльний аналіз технічних характеристик і параметрів горизонтальних і вертикальних парогенераторів для реакторних установок з водним теплоносієм сучасних енергоблоків АЕС потужністю 1000 МВт. Зазначено, що на особливості конструктивних схем і конструкцій парогенераторів енергоблоків АЕС з водними теплоносіями великий вплив робить існування сильної залежності між температурою цих теплоносіїв на вході в парогенератор та їх тиском в контурі реактора. Відмічено, що конструкції і характеристики горизонтальних парогенераторів енергоблоків АЕС потужністю 1000 МВт обмежують можливості подальшого підвищення техніко-економічних показників. Визначено, що прямотечійні вертикальні парогенератори з гідравлічною схемою, що передбачає рух робочої речовини в трубках, а водного теплоносія – в міжтрубному просторі, за своїми габаритними і масовими характеристиками значно поступаються прямотечійним вертикальним парогенераторам з водним теплоносієм в трубках, а за масою – також і вертикальним парогенераторам з природною циркуляцією.
Порівняльний аналіз техніко-економічних і масогабаритних характеристик горизонтальних та вертикальних парогенераторів енергоблоків АЕС потужністю 1000 МВт
Keywords: nuclear power plant units; horizontal and vertical type steam generators; steam parameters; water coolants; working substances; technical and weight characteristics; енергоблоки АЕС; парогенератори; технічні і масогабаритні характеристики; параметри пари; водні теплоносії; робочі речовини